(untitled) (American International Journal of Supply Chain Management, 2021)
As a basic unit of kinship relationships, the family plays a significant role in every Nigerian society. With the occurrence of social change in every society in the contemporary period, Nigerian traditional family structure and setting have undergone significant alterations as a consequence of the influx of the superfluous forces through globalisation. The sole objective of this review was to pinpoint the cultural aspects of the indigenous family system that technological, socio-cultural and economic factors, as components of globalisation, have altered in Nigerian society. In this systematic review, integration of a large body of both quantitative and qualitative findings from previous relevant studies was carried out to achieve the sole objective of this study. Via the available relevant previous studies, this systematic review concluded that several family structures and settings, such as mate selection, family size, family settlement and resident rule (from patrilocal to neolocal), child rearing as well as relationship between work and family role of gender have undergone changes while new pattern of family structure and setting such as non-marital childbearing, single parenthood, non-marital unions, cohabiting couples, single parent family, blended family or contract marriage, homosexual couples are on the increase in the country.